2001
DOI: 10.1046/j.1440-1614.2001.00964.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mental Health of Young People in Australia: Key Findings from the Child and Adolescent Component of the National Survey of Mental Health and Well-Being

Abstract: Child and adolescent mental health problems are an important public health problem in Australia. The appropriate balance between funding provided for clinical interventions focusing on individual children and families and funding for interventions that focus on populations, requires careful study. The latter are an essential component of any strategy to reduce mental health problems as the high prevalence of problems makes it unlikely that individual care will ever be available for all those needing help. Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
520
12
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 601 publications
(573 citation statements)
references
References 18 publications
(23 reference statements)
23
520
12
9
Order By: Relevance
“…The mean scores observed in the current study may appear disproportionately higher than prevalence rates previously reported by previous studies of both Indian adolescents (7,12) as well as North American or Australian adolescents (44,45). However, it is important to distinguish such studies on the basis that these previous studies reported the prevalence of adolescents meeting the full diagnostic criteria for depressive disorders, such as Major…”
Section: Differences In Levels Of Symptomscontrasting
confidence: 72%
“…The mean scores observed in the current study may appear disproportionately higher than prevalence rates previously reported by previous studies of both Indian adolescents (7,12) as well as North American or Australian adolescents (44,45). However, it is important to distinguish such studies on the basis that these previous studies reported the prevalence of adolescents meeting the full diagnostic criteria for depressive disorders, such as Major…”
Section: Differences In Levels Of Symptomscontrasting
confidence: 72%
“…In longitudinal studies using semistructured interviews and standardized diagnostic criteria, 10-year point prevalence and lifetime prevalence rates of psychiatric disorder in diabetic youth were found to be 47% (19) and 37% (23), respectively. These disorder rates are two to three times higher than those found in the general community (73,74).…”
contrasting
confidence: 55%
“…Other studies put rates of psychological distress in Australian children higher, across a broad age range 21, 44, 45, 46…”
Section: Discussionmentioning
confidence: 97%